From steam to diesel : managerial customs and organizational capabilities in the twentieth-century American locomotive industry - Churella, Albert J., 1964- (Princeton studies in business and technology., 1998)
A comparative work of business history and the history of technology, the book is not a complete history of any locomotive builder, nor does it explore the origins of the diesel engine in great detail. What it does is to demonstrate how managers addressed radical shifts in technology and production methods. Churella reveals that managerial culture and corporate organizational routines, more than technological competency per se, allowed some companies to succeed, yet constrained the actions of others. He details the shift from small-batch custom manufacturing techniques in the steam locomotive industry to mass-production methods in the diesel locomotive industry.